Construction training process of highly skilled players in mini-football for competition period - Stasiuk I.I (Kharkov National Pedagogical University, 2013)
Analyzed the structure and content of the competition period in mini-football. It was determined that the structure of the competition period consists of 4 competitive mesocycles. In each mesocycle includes various types of micro-cycles (competitive, cross-game and rehabilitation). Reflects the ratio of specific and non-specific (general preparations) means training work. So in the competitive period for competitive mesocycles general preparations exercises ranged from 38.3 to 42.4%, special-preparation - from 29.9 to 32.6%, competitive - from 20.9 to 23.3%. The intensity of the training load in intergame microcycles less than competitive. This corresponds to the strategy of building the training process in the competitive period. During the competition period the ratio of the training load was: aerobic focus - 49.2%, mixed - 46.1%, anaerobic alactate - 2.4%, anaerobic glycolytic - 2.3%. Defines the scope and focus of the training load: longer the aerobic work, then - mixed, anaerobic- alactate and anaerobic-glycolytic. The comparative characteristics of the intensity of the training load in competitive and intergame microcycles.